Rheological characteristics of cement-sodium silicate grout in its fluid–solid phase transition process. (2nd January 2023) - Lianzhen, Zhang; Xu, Han; Qingsong, Zhang; Yuntian, Chu; Jun, Liu
Highlights: Rheological properties of CS grout in its fluid–solid transition process were measured. Influences of W/C mass ratio and C/S volume ratio on viscosity and yield stress were investigated. Rheological constitutive model of CS grout in its fluid–solid phase was established. Abstract: The rheology of quick-setting grout during the phase transition from fluid to solid is a key factor for consideration in grouting diffusion design. In this paper, cement-sodium silicate grout (CS grout) was used in the experiment as a typical quick-setting grout. The rheological properties of quick-setting grout during the entire phase transition period, including phase transition time, grout viscosity, and yield stress, were investigated. The influences of water-cement mass ratio (W/C mass ratio) and cement-sodium silicate ratio (C/S volume ratio) on rheological properties of quick-setting grout were analyzed. Results show that gel reaction process of CS grout can be divided into three stages: fluid phase, fluid–solid phase, and solid phase. Among them, shear stress of CS grout increased rapidly with phase transition from fluid to fluid–solid state. The rheological constitutive relation of CS grout always belonged to the Bingham model with W/C mass ratio ranging from 0.8 to 2.0 and C/S volume ratio ranging from 1 to 3. A rheological model of CS grout was presented, among which the relationship between rheological parameters and reaction time is expressed by exponential functions.